Handbook of Critical Care - Hall, Jesse B. (Springer London : Imprint: Springer, 2009)
Critical care is an exciting field with diverse and complex challenges. These challenges include identifying pathophysiology in the individual patient, integrating care providers from multiple disciplines, addressing social concerns in the sick or dying patient, to name but a few. As a result of this complexity, care in the intensive care unit must be guided by a thoughtful and organized approach. Written as a teaching aid for residents and fellows in intensive care and emergency medicine, this revised edition of the Handbook of Critical Care is also a valuable reference for all medical professionals in the critical care team. The 15 chapters in this pocket-sized basic intensive care manual include eight substantial sections covering the major organ systems, as well as infection, nutrition, physical injury and toxicology, and brief chapters on scoring systems and obstetrics. The chapters feature numerous pictures, comparative tables, diagrams and lists, and provide essential information for juniors training in intensive care medicine. The definitions, etiology, clinical features and differential diagnoses are well covered, while extensive use of bullet points and numbering increases the clarity of presentation enabling readers to quickly get to the key learning points.